(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Microscopy, macroscopy, physicochemical analysis, preliminary phytochemical screening for standardization of Dolichos lablab (FABACEAE) seeds were performed. The seeds are roughly trapezoidal and flattish, with quite thin cotyledons. The hylum is small and linear which gets located in a small depression on the seed’s lateral margin. Microscopic evaluation revealed that the epidermis is single – layered, brown, thin walled and shining, because of mucilage in this layer. Endosperm forms bulk of the seed with thick-walled parenchyma. Outer portion of the seed contains alueron grains which are protein in nature. Preliminary phytochemical screening showed the presence of steroids, tannins, proteins amino acids flavonoids, terpenoids, mucilage, volatile oil, saponin and carbohydrates.